The effectiveness of immediate implant placement for single tooth replacement compared to delayed implant placement: A systematic review and meta‐analysis. (18th June 2019) - Cosyn, Jan; De Lat, Liesa; Seyssens, Lorenz; Doornewaard, Ron; Deschepper, Ellen; Vervaeke, Stijn
Abstract: Aim: To compare immediate implant placement (IIP) to delayed single implant placement (DIP, ≥3 months post‐extraction) in terms of implant survival (primary outcome), surgical, clinical, aesthetic, radiographic and patient‐reported outcomes (secondary outcomes). Materials and Methods: Two reviewers independently performed an electronic search in PubMed, Web of Science, EMBASE and Cochrane and a hand search to identify eligible studies up to May 2018. Only randomized controlled trials (RCTs) and non‐randomized controlled studies (NRSs) comparing IIP to DIP with at least 1 year of follow‐up were selected for a qualitative analysis and meta‐analysis. Results: The search identified 3 RCTs and 5 NRSs out of 2, 589 titles providing data on 473 single implants (IIP: 233, DIP: 240) that had been in function between 12 and 96 months. One RCT showed unclear risk of bias, whereas all other studies demonstrated high risk. Meta‐analysis showed significantly lower implant survival for IIP (94.9%) as compared to DIP (98.9%) (RR 0.96, 95% CI [0.93; 0.99], p  = 0.02). All were early implant failures. A subgroup meta‐analysis demonstrated a trend towards lower implant survival for IIP when postoperative antibiotics had not been administered (RR: 0.93, 95% CI [0.86; 1.00], p  = 0.07). This was not observed among studies including the administration of postoperative antibiotics (RR: 0.98, 95% CI [0.94; 1.02], p  = 0.35). Meta‐analyses showed similar probing depth (WMD 0.43 mm, 95% CI [−0.47; 1.33], p  = 0.35) and aesthetic outcomes as assessed by the pink aesthetic score (standardized WMD −0.03, 95% CI [−0.46; 0.39], p  = 0.88) for IIP and DIP. Data on marginal bone loss were conflicting and highly biased. Soft tissue recession was underreported and available data were highly biased. Patient‐reported outcomes were underreported, yet both IIP and DIP seemed well tolerated. Conclusion: Immediate implant placement demonstrated higher risk for early implant loss than DIP. There is a need for RCTs comparing IIP to DIP with CBCT analyses at different time points and data on midfacial recession with the preoperative status as baseline. In these studies, the need for hard and soft tissue grafting should also be evaluated.